Learning Islamic Education Online - Sopiah, Sopiah (Jurnal Edusci, 2024)
The COVID-19 pandemic has forced educational institutions around the world to shift to online learning. However, the impact of online learning on Islamic Religious Education (PAI) learning in secondary schools is still poorly understood. This study aims to evaluate the achievement of student competence in online PAI learning. This study used a qualitative approach with primary and secondary data from teachers, supervisors, and students in several secondary schools. The results showed that online PAI learning tends to be more oriented towards text comprehension, ignoring students' affective aspects, and eliminating social interaction in the learning process. Independent individual learning, lack of teacher-student interaction, and time restrictions also have an impact on neglecting the affective dimension of students. The implication of this finding is that online PAI learning has not been able to achieve overall learning objectives, especially in the development of students' cognitive, affective, and psychomotor competencies. It is necessary to adjust learning strategies so that online PAI learning can be more effective and meaningful for students in the future.